2016
DOI: 10.1371/journal.pone.0147582
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death in the Epithelia of the Intestine and Hepatopancreas in Neocaridina heteropoda (Crustacea, Malacostraca)

Abstract: The endodermal region of the digestive system in the freshwater shrimp Neocaridina heteropoda (Crustacea, Malacostraca) consists of a tube-shaped intestine and large hepatopancreas, which is formed by numerous blind-ended tubules. The precise structure and ultrastructure of these regions were presented in our previous studies, while here we focused on the cell death processes and their effect on the functioning of the midgut. We used transmission electron microscopy, light and confocal microscopes to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…Sonakowska et al () observed three modes of cell death in the midgut proper and hepatopancreas of Neocaridina davidi , namely necrosis, apoptosis, and autophagy. They found apoptosis mainly in the anterior part of the intestine, and autophagy mainly in the proximal region of the hepatopancreas tubules, that is, in the oldest cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sonakowska et al () observed three modes of cell death in the midgut proper and hepatopancreas of Neocaridina davidi , namely necrosis, apoptosis, and autophagy. They found apoptosis mainly in the anterior part of the intestine, and autophagy mainly in the proximal region of the hepatopancreas tubules, that is, in the oldest cells.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatopancreas of the Decapoda may serve as a comparative model for biologists studying the digestive systems of other animals, particularly invertebrates. It may also be of some value for investigating more general topics such as stem cell activity (Vogt, ), cell aging (Vogt, ), and cell death (Sonakowska et al, ). The polar architecture of the heptopancreas tubules with terminal stem cells and the distinct age gradient along the tubules offer particularly good conditions for such investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three types are best known: apoptosis, necrosis and autophagy. They are common processes that occur in the digestive epithelia of invertebrates (Malagoli et al 2010; Franzetti et al 2012; Romanelli et al 2014, 2016; Wilczek et al 2014; Lipovšek and Novak 2015; Rost-Roszkowska et al 2015, 2016; Sonakowska et al 2016). When the cytoplasm is rich in autophagic structures, apoptosis and/or necrosis is activated (Levine and Yuan 2005; Giusti et al 2007; Tettamanti et al 2007; Rost-Roszkowska et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…It is digested due to autophagy so numerous autophagic structures have been detected in the cytoplasm of the digestive cells during the later stages of oogenesis, which suggests the participation of this accumulated material in vitellogenesis and choriogenesis (Rost-Roszkowska et al 2011). The reserve material is commonly accumulated in the cytoplasm of the digestive cells in insects (Lipovšek et al 2011; Amiri and Bandani 2013; Lipovšek and Novak 2015), myriapods (Chajec et al 2012, 2014; Sosinka et al 2014), crustaceans (Sousa and Petriella 2000; Sonakowska et al 2016) and tardigrades (Rost-Roszkowska et al 2011; Hyra et al 2016). It can be exploited due to digestion that involves autophagy during the natural periods of starvation such as the hibernation (Lipovšek et al 2011; Kamińska et al 2016), molting (Franzetti et al 2012; Romanelli et al 2014, 2016) or during starvation that is caused by a lack of food in the environment in which the animal lives (Zaffagnini and Martens 2016).…”
Section: Discussionmentioning
confidence: 99%